2020
DOI: 10.1002/admi.201901682
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments on Emerging Properties, Growth Approaches, and Advanced Applications of Metallic 2D Layered Vanadium Dichalcogenides

Abstract: The electronic structures of transition metal dichalcogenides (TMDs) has a strong dependency on the d‐band electrons of the central metal (M) atom. In particular, trigonal prismatic coordinated (2H) and octahedral coordinated (1T) phases with distinct crystal structure‐property relationships. Extraordinarily diverse electrical properties ranging from semiconducting, semimetallic to intrinsic metallic basically underlie from different Fermi level locations. Amid all TMDs, most specifically metallic VX2 possess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 155 publications
(215 reference statements)
0
24
0
Order By: Relevance
“…The hydrothermal method is a bottom–up synthesis method using water as the reaction medium to obtain high‐yield ultra‐thin 2D m‐TMDs. [ 238 ] In Figure a, the reactants, water, and surfactants are mixed at room temperature and then placed in a sealed container. The temperature of the reaction system must be higher than the boiling point of the solvent, which can promote the generation of high pressure and further improve the crystallinity of m‐TMDs.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…The hydrothermal method is a bottom–up synthesis method using water as the reaction medium to obtain high‐yield ultra‐thin 2D m‐TMDs. [ 238 ] In Figure a, the reactants, water, and surfactants are mixed at room temperature and then placed in a sealed container. The temperature of the reaction system must be higher than the boiling point of the solvent, which can promote the generation of high pressure and further improve the crystallinity of m‐TMDs.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…A broad class of materials having a formula MX 2 (where M represents the transition-metal element of group IV or V or VI and X represents the chalcogen, i.e. , S or Se or Te atom). , Their extraordinary features like tunable electronic properties, unusual physiochemical (thickness-controlled), optical (tunable band gap), high mechanical strength, and so on, particularly, mono- and multi-layered TMDs hold great opportunity to explore in a variety of applications . Owing to these excellent properties, TMDs have been explored in a wide variety of applications such as in supercapacitors, , batteries, , energy conversion, , sensors, catalysis, field emission, photovoltaic, and electronics and optoelectronic devices. , The M–X possesses strong covalent bonds to be arranged in the X–M–X layered morphology, while weak van der Waals interaction dominates between two MX 2 layers featuring two-dimensional (2D) layered like structures .…”
Section: Introductionmentioning
confidence: 99%
“…Nonstoichiometric 2D materials with curved edge structures are critical for the intrinsic magnetic and spin-dependent properties. [84][85][86][87] Theoretical studies demonstrated that the magnetic properties in TMDs such as MoS 2 , VS 2, and VSe 2, etc. arise from the unsaturated transition metal and S/Se atoms at the edges.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…arise from the unsaturated transition metal and S/Se atoms at the edges. [87][88][89][90][91] Hence, the vertically aligned 2D layered materials are ideal candidates for tunable magnetic properties due to the presence of an abundant number of open edges and defects on its surface. Vertically aligned edges of MoS 2 nanobelts showed room-temperature ferromagnetic properties with the magnetization of 0.055 emu g −1 at an applied field of 1T, which was ≈50 times larger than that of solution exfoliated MoS 2 .…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation